THE UTILIZATION OF FACEBOOK AND WHATSAPP AS DIGITAL MARKETING STRATEGIES FOR AGRICULTURAL PRODUCTS IN EAST BULANGO DISTRICT, BONE BOLANGO REGENCY - Riski Mato; Sudarsono; Sitti Husna Noviana Djou (Journal of Economic, Business, and Administration (JEBA), 2026)
This study aims to analyze the utilization of Facebook and WhatsApp Messenger as marketing media for agricultural products in East Bulango District, Bone Bolango Regency. Specifically, the study examines the role of Facebook in product promotion and information dissemination, explores the benefits of WhatsApp in facilitating communication and transactions between farmers and consumers, and identifies the supporting and inhibiting factors affecting the implementation of digital marketing strategies. This research employed a descriptive qualitative approach. Data were collected through in-depth interviews, observation, and documentation involving five purposively selected informants consisting of conventional farmers, digital farmers, and agricultural collectors. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. The findings indicate that Facebook serves as the primary platform for promoting agricultural products and expanding market reach, while WhatsApp facilitates direct communication, price negotiation, order confirmation, and transaction coordination. The use of these platforms enables farmers to obtain higher selling prices and reduce dependence on intermediaries. However, several challenges remain, including limited digital literacy, time constraints, logistical difficulties, challenges in marketing large product volumes, and low consumer interest in unbranded products. The study concludes that Facebook and WhatsApp have significant potential to support agricultural marketing in rural areas, although greater institutional support is needed through digital literacy training, marketing assistance, and infrastructure development to encourage wider adoption.